2020
DOI: 10.1186/s12864-020-07169-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation in infants with low and high body fatness

Abstract: Background Birth weight is determined by the interplay between infant genetics and the intrauterine environment and is associated with several health outcomes in later life. Many studies have reported an association between birth weight and DNA methylation in infants and suggest that altered epigenetics may underlie birthweight-associated health outcomes. However, birth weight is a relatively nonspecific measure of fetal growth and consists of fat mass and fat-free mass which may have different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…More than half of the studies (N = 12) considered important confounders (age, sex, and white blood cell composition) in the analyses. Overall, 19 studies out of 23 found an association between childhood anthropometric parameters with at least one methylated CpG site or region (no significant epigenomewide association at all was found in just four studies 21,30,33,34 ). The main outcomes investigated included obesity (N = 10), BMI (N = 9), skinfold thickness (N = 1), and fat mass (N = 2) in children over 1 year, while one study examined catch-up growth at 12 months.…”
Section: Epigenome-wide Association Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…More than half of the studies (N = 12) considered important confounders (age, sex, and white blood cell composition) in the analyses. Overall, 19 studies out of 23 found an association between childhood anthropometric parameters with at least one methylated CpG site or region (no significant epigenomewide association at all was found in just four studies 21,30,33,34 ). The main outcomes investigated included obesity (N = 10), BMI (N = 9), skinfold thickness (N = 1), and fat mass (N = 2) in children over 1 year, while one study examined catch-up growth at 12 months.…”
Section: Epigenome-wide Association Studiesmentioning
confidence: 98%
“…Illumina arrays were the most widely used technique (N studies = 17 out of 23 studies), while a few studies used enzyme digestion-based tagging assay, 19,20 reduced representation bisulfite sequencing, 21 chromatin immunoprecipitation combined with DNA microarray, 22 targeted bisulfite sequencing, 23 and methylated DNA immunoprecipitation sequencing. 24 Peripheral blood was the most analyzed sample type (N = 15 studies), while a few studies used cord blood (N = 4 studies), 22,[25][26][27] saliva or buccal cells (N = 4 studies), 23,[28][29][30] neonatal blood spots samples (N = 1 study), 31 and placenta (N = 1 study). 32 The sample size of studied populations varied from 7 to 4133 children, which in most cases were European (N = 11) or from North America (N = 8), with low representation of other countries (N = 2 studies took place in Australia and 2 in China).…”
Section: Epigenome-wide Association Studiesmentioning
confidence: 99%